Tinjauan Yuridis terhadap Kedudukan Badan Usaha Milik Desa (BUMDes) Berdasarkan Peraturan Pemerintah Nomor 11 Tahun 2021 - Rizky Aditya Saputra; Aidul Fitriciada Azhari; Nuria Siswi Enggarani (CV Rewang Rencang, 2025)
Village-Owned Enterprises, known by the abbreviation BUMDes, are a form of business formed and run by the village government. Regulations related to BUMDes have undergone various changes over time. Law Number 11 of 2020 is the latest legal basis governing the development, establishment, mechanisms, and position of BUMDes. These regulations are then further elaborated through Government Regulation (PP) Number 11 of 2021 as its implementing regulations. Therefore, it is important to conduct further discussion regarding the essence of PP No. 11 of 2021 concerning the implementation of BUMDes, as well as to assess whether BUMDes can be categorized as a legal entity after this regulation comes into effect.